The effect of plyometric exercises on repeated strength and power performance in elite karate athletes - Margaritopoulos, S.; Theodorou, A.; Methenitis, S.; Zarasa, N.; Donti, O.; Tsolakis, C. (Journal of Physical Education and Sport, 2015)
Objective: To explore the participation and attitude of institutionalised elderly towards Physical Activity. The purpose of this study was to evaluate the effects of a plyometric protocol on round kick force and lower limbs` jumping performance in elite karate athletes and to examine whether this plyometric protocol could be used over repeated trials in competitive warm up conditions. Ten elite level karate athletes (5 males and 5 females) were randomly assigned to an intervention or a control condition of inactivity. The intervention condition consisted of 3 sets of 5 tuck jumps and was repeated over three trials interspersed by ten min of rest. Round kick force, and counter movement jump (CMJ) height, power, relative power, force and rate of force development (RFD) were measured at the beginning and after each trial. The two-way 2x4 repeated measures ANOVA revealed significant condition x time interaction for CMJ height (F= 6.510, p=0.02, ç2=0.736). No main effects for time or between conditions were observed, however, CMJ height after the third trial was increased (+3.5%, p<0.003) compared to baseline performance. Significant correlations were found between round kick force and lower limbs` jumping performance. The results of this study may provide useful information for competitive warmingup strategies in contact sports where strength and power are crucial determinants throughout repetitive successive efforts.